UJI AKTIVITAS IMUNOSTIMULATOR EKSTRAK DAUN SIRIH MERAH (Piper crocatum Ruiz.& Pav.) PADA Cortunix sp. YANG TERINDUKSI VAKSIN AI SUBTIPE H5N1 MELALUI PENGUKURAN TITER ANTIBODI IgY - Ely Muji Lestari (PSF 15 UMY 527, 2015)
*527 Avian Influenza (AI) or well known as bird flu is a disease caused by influenza viruses type A that habitually attack birds. This disesase is a zoonotic disease, its means the disease can be transmitted from animals to humans. Some preventive effort to handling AI has been held due to its harmful, such as increasing antibody level of birds. One of alternatives materials that can be used to increased antibody level poultry is red betle (Piper crocatum Ruiz.& Pav.). The purpose of this study is to determine the effect of Piper crocatum Ruiz.& Pav. (PCRP) on the production of IgY anti-AI from Cortunix sp. that induced AI vaccine subtype H5N1. Piper crocatum Ruiz.& Pav. in this study was identified using thin layer chromatography (TLC). This research was used experimental method. Animal test in this study was 15 quail of Coturnix sp. which divided into 5 groups, the first group as K0: without treatment, second group is K (-) as negative control this group induced with AI vaccine (VAI), third group as PCRP 10 mg/quail/day, fourth group as PCRP 20 mg/quail/day and fifth group as PCRP 30 mg/quail/day. Vaccination was given 7 days after conditioning with concentrate 0,2 ml by intramuscular. Vaccination was repeated 2 times with the same dosage in a 4 weeks intervals. Sampling conducted at 4tdand 8th weeks. IgY anti-AI isolated by PEG precipitation method. The levels IgY anti-AI was measured by haemaglutination inhibition test. Data were analyzed with Shapiro-Wilk normality test and then continue with Kruskal-Wallis and Mann-Whitney test. The result of thin layer crhomatography (TLC) showed that Piper crocatum Ruiz.&. Pav. contains with flavonoids and terpenoids compound. Mann-Whitney test showed the different significant between PCRP 10 mg/quail/day and PCRP 20 mg/quail/day against VAI (p<0,05). It be conclude that the ethanolic extract of Piper crocatum Ruiz.& Pav. can increase the number of IgY antibody titers with effective dose as an immunostimulatory agent concentrate 10 mg/quail/day. Key words: Avian Influenza, Piper crocatum Ruiz.& Pav., Coturnix sp., IgY